Research on the Decision-Making of the Battery Swapping Supply Chain Considering Battery Standardization Under the Battery Swapping Model - Li, Chao (Asia Pacific Economic and Management Review, 2025)
This paper examines the battery swapping supply chain comprising battery manufacturer, vehicle manufacturer, and battery swapping operator, focusing on scenarios where battery standardization is led either by the battery manufacturer or by the battery swapping operator. Optimal decisions are derived for both battery standard-setting modes, followed by a comparative analysis. The findings reveal that when the battery swapping operator leads the formulation of battery standards, it results in greater benefits for both the battery manufacturer and battery swapping operator, while also facilitating the adoption of battery-swapping vehicles. However, the optimal strategy for the vehicle manufacturer is influenced by the battery standardization cost coefficient. Although battery swapping operator-led battery standardization enhances the level of battery standardization, it also increases the cost of battery-swappable vehicle bodies. Furthermore, an increase in the battery standardization cost coefficient reduces firm profitability, whereas greater sensitivity to battery standardization positively impacts corporate profits.